97.6k views
3 votes
Resolve:

1:3a + 2a
2:-5b -7b
3:-a² -9a²
4:3a^x-²^+5a^x-²
5:18x - 11x
6:5a - 8a + a -6a + 21a​

1 Answer

3 votes


\bold{1: 3a + 2a \: = 5a}


\bold{2: - 5b - 7b = - 12b}


\bold{3: - a {}^(2) - 9 a{}^(2) = - 10a {}^(2)}


\bold{4: 3a {}^(x - 2) + 5a {}^(x - 2) = 8a {}^(x - 2)}


\bold{5: 18x - 11x = 7x}


\bold{6: 5a - 8a + a - 6a + 21a = 13}

The reduction of similar terms is an operation that aims to convert two or more similar terms into a single term.

In these cases you must add or subtract either addition, subtraction or subtraction and addition, using the law of signs.


\begin{gathered} \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: {\bold{Law \: of \: signs: }} \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: + * + = + \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: - * + = - \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: + * - = - \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: - * - = + \end{gathered}

User Kennypu
by
4.6k points